Phlorizin administration ameliorates cognitive deficits by reducing oxidative stress, tau hyper‐phosphorylation, and neuroinflammation in a rat model of Alzheimer's disease. Issue 6 (25th September 2018) - Tian, Yuan; Lu, Weibing; Deng, Haohua; Yang, Fan; Guo, Yan; Gao, Ling; Xu, Yancheng
Abstract: Phlorizin is a member of the chalcone class of organic compounds that was originally extracted from apples. Phlorizin also exhibits various bio‐activities, such as anti‐diabetes, anti‐oxidation and anti‐obesity. However, the effects of phlorizin on cognitive deficits or Alzheimer's disease (AD) are still unclear. Herein, we investigated its effects on Aβ‐induced cognitive deficits in a Aβ‐induced rat model of AD. Dietary treatment of 0.02% phlorizin for 10 weeks dramatically improved the learning and memory abilities during the Morris water maze test in AD rats. Mechanism studies suggested that phlorizin alleviated oxidative stress, tau hyper‐phosphorylation, and neuro‐inflammation in brain of rats. This research provides novel insight into the treatment effect of phlorizin on AD. Practical applications: Phlorizin belongs to the chalcone class of organic compounds that is adundant in various plants especially apples. Literatures have proved the anti‐oxidation, anti‐inflammation, anti‐diabetes and anti‐obesity activites of phlorizin. The current study firstly demonstrated dietary treatment of 0.02% phlorizin for 10 weeks dramatically improved the learning and memory abilities of AD rats by alleviating oxidative stress, tau hyper‐phosphorylation, and neuro‐inflammation in brain. Phlorizin may serve as a novel pratical bioactive compound in the treatment Alzheimer's disease.